Efektivitas Keterlibatan Penyusunan Key Perfomance Indicator dalam Menurunkan Tingkat Resistensi terhadap Perubahan Sasaran Kinerja - Nina Fitriana; Alimatus Sahrah; Reny Yuniasanti (JIP (Jurnal Intervensi Psikologi), 2017)
This research aims to examine the effectiveness of involvement in arranging key performance indicator to decrease of resistance to change level towards performance target for management trainee in University X. The subject of this research is management trainee consisting of experiment group and control group. The experiment group comprised of 16 people while the control group consisted of 8 people. The subjects of this research have at least master degree, work contract, and medium to high level of resistance to change fortarget performance. The research design used pretest posttest control group design. The data collection is conducted using scale of resistance to change for taget performance. The finding of this research indicated that the involvement in arranging key performance indicator is effective in decreasing the resistance to change level towards performance target for management trainee in University X.Key words: resistance to change, involvement, key performance indicator